Heterologous expression, biochemical characterisation and computational analysis of Bacteroides fragilis enolase - MUTLU, ÖZAL (My University, 2022)
© 2022Bacteriodes fragilis is an anaerobic bacterium found in the human intestinal flora. In this study, BfEno was targeted with a structure-based drug design approach because inhibition of this enzyme may prevent both the aerobic and anaerobic pathways due to its role in the glycolytic pathway. First, the gene encoding BfEno was cloned, expressed and the protein produced over 95% purity. The Km and Vmax values of BfEno were determined as 314.9 µM and 256.2 µmol/min.mg, respectively. Drug-like chemicals were retrieved from the ZINC database for high-throughput virtual screening analyses. As a result of screening study, the ZINC91441604 has been proposed to bind to the active site of the enzyme and remain stable. The same compound exhibited weak binding to the human enolases than the bacterial enolase. Hence, ZINC91441604 may be proposed as a novel candidate for further in vitro and in vivo drug analysis towards the treatment of B. fragilis infections.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Matematik; Moleküler Biyoloji ve Genetik; KİMYA, ORGANİK; MATEMATİK, DİSİPLİNLERARASI UYGULAMALAR; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; MATHEMATICS; MOLECULAR BIOLOGY & GENETICS; CHEMISTRY, ORGANIC; MATHEMATICS, INTERDISCIPLINARY APPLICATIONS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Organik Kimya; Fizik Bilimleri; Hesaplamalı Matematik; Structural Biology; Organic Chemistry; Physical Sciences; Computational Mathematics; Antibiotic resistance; Bacteriodes fragilis; Enolase; Enzyme kinetic; In silico studies; Structure-based drug design